A qualitative investigation of factors influencing successful reward-based crowdfunding campaigns in the UK and China. Issue 1 (2nd January 2022) - Hou, Yilin; Phillips, Robert A.
ABSTRACT: Crowdfunding is a means of accessing funding for a new project in exchange for equity, interest payments, or nonmonetary rewards that can be physical or digital. It is different from traditional funding in the sense that it relies on large numbers of people investing small sums of money, making it less risky for individual investors, rather than a large sum from a venture capitalist. We interviewed project founders in the United Kingdom and China and the similarities and differences between successful reward-model campaigns were analyzed. It was found that, while there are several similarities, there were some interesting differences. For example, Chinese founders hired click farmers to push their project up the rankings on the crowdfunding site, used certain colors that had cultural significance in their pitch, and a heavily discounted preorder was suggested as the best way of enticing a relatively risk-averse crowd. This article should help those project founders who are considering a crowdfunding campaign in either country to maximize their chances of success.